Lithium alloy negative electrode with reserved space and integrated conductive skeleton and preparation method
By building a reserved space and an integrated conductive framework on the lithium alloy negative electrode, the problems of uneven deposition and volume change of metal lithium negative electrode during the circulation process are solved, and the high cycling performance and safety of the battery are achieved.
Patent Information
- Application Number
- CN202211506981.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-11-28
AI Technical Summary
The metal lithium negative electrode is caused by uneven deposition during the circulation process, which leads to lithium dendrites, piercing the separator and causing a short circuit in the battery. The volume changes greatly during the charging and discharging process, reducing the battery cycle life.
A lithium alloy negative electrode with reserved space and an integrated conductive framework is designed. By constructing a three-dimensional alloy skeleton layer on the upper part of the electrode, a stable deposition frame is provided, which inhibits the growth of lithium dendrites and maintains the volume of the negative electrode constant.
Through the reserved space and integrated conductive framework structure, uniform deposition and volume stability of metal lithium are achieved, significantly improving the cycling performance and safety of the battery.
Smart Images

Figure CN115732639B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium alloy negative electrode with a reserved space and an integrated conductive skeleton and a preparation method thereof. Background Art
[0002] At present, in recent years, new technologies have continuously emerged in the process of commercial application of lithium-ion batteries, and they have been widely used in energy storage devices such as computers, mobile phones and electric vehicles. On the other hand, the metal lithium negative electrode is an ideal negative electrode material for replacing the carbon negative electrode in lithium-ion batteries and building the next generation of high energy density lithium secondary batteries because of its high energy density (3860mAh / g) and extremely low redox potential (-3.04V vs. standard hydrogen electrode). However, the metal lithium negative electrode has the safety problem of uneven deposition during the cycle, which leads to the growth of lithium dendrites and eventually pierces the diaphragm and causes battery short circuit. In addition, during the charge and discharge process, due to the non-dense deposition of metal lithium, the metal lithium negative electrode is often accompanied by a relatively large volume change, resulting in the overall deformation of the battery structure, which in turn greatly reduces the cycle life of the battery and fails to meet the requirements of practical application.
[0003] At present, in order to solve these problems of metal lithium negative electrode, researchers have done a lot of modification research, such as using electrolyte additives to form a protective film on the surface of metal lithium or using lithium alloy negative electrodes with higher stability and inducing metal lithium deposition. However, these modification methods all result in a "solid" metal lithium negative electrode with a dense structure and a flat electrode surface. The flat and dense surface of the metal lithium negative electrode makes it difficult to exert various modification effects inside the electrode, and has no constraint on the deposition of lithium, resulting in the subsequent deposition of metal lithium can only accumulate on the surface of the metal lithium negative electrode, and then grow into lithium dendrites, and produce a large volume change. Therefore, it is a new trend to reserve a certain space on the surface of the metal lithium negative electrode, form a "hollow" structure on the upper part of the electrode to accommodate lithium deposition, maintain the constant volume of the negative electrode during the charge and discharge process, and use the conductive skeleton structure on the surface to regulate the deposition and growth behavior of lithium, thereby improving the cycle performance of the battery.
[0004] Through the above analysis, the problems and defects of the existing technology are: the flat and dense surface of the metal lithium negative electrode makes it difficult to play various modification effects inside the electrode, and there is no constraint on the deposition of lithium, resulting in the subsequent deposition of metal lithium can only accumulate on the surface of the metal lithium negative electrode, and then grow into lithium dendrites, and produce a large volume change. Obviously, the morphology of the skeleton structure required to construct the "hollow" structure on the upper part of the electrode, the type of material and the connection with the lower part of the electrode have a crucial impact on the performance of the lithium negative electrode. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a lithium alloy negative electrode with a reserved space and an integrated conductive skeleton and a preparation method thereof.
[0006] The present invention is implemented as follows: a lithium alloy negative electrode with a reserved space and an integrated conductive skeleton comprises:
[0007] The lower layer of the negative electrode is provided with a lithium-rich alloy layer, and the lithium-rich alloy layer contains a three-dimensional skeleton formed by a lithium solid solution / intermetallic compound phase. The upper layer of the lithium alloy negative electrode is a reserved space formed by the remaining three-dimensional alloy skeleton and the gaps between the skeletons. The skeleton in the surface reserved space and the skeleton in the lithium alloy are both three-dimensional integrated skeleton structures formed in situ by lithium solid solution or intermetallic compound.
[0008] Furthermore, the lithium solid solution or intermetallic compound three-dimensional skeleton is formed in situ during the preparation of the lithium alloy and is a continuous integrated structure.
[0009] Furthermore, the height of the reserved space on the surface, that is, the thickness of the alloy skeleton layer reserved on the surface, is 1 to 100 μm.
[0010] The present invention also provides a method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton, and the specific preparation method comprises:
[0011] Step 1: Mix the dissimilar metal / non-metal with metallic lithium in a certain molar ratio, and melt them into a liquid at 300°C to 800°C to form a molten lithium-rich alloy;
[0012] Step 2: The obtained molten lithium-rich alloy is formed on a metal foil to obtain a lithium-rich dual-phase alloy layer with uniform thickness;
[0013] Step 3: preparing a specific organic solution that can react with metallic lithium;
[0014] Step 4: Soak the obtained lithium alloy negative electrode in a specific organic solution, and obtain reserved space layers with different thicknesses by controlling the solvent concentration and reaction time.
[0015] Furthermore, the dissimilar metal / non-metal includes one or more of Cu, Al, Sn, Zn, Mg, Ca, Ba, Ag, In, Ge, Pb, Sb, C, and Si.
[0016] Furthermore, the time for cooling the obtained lithium-rich dual-phase alloy layer to room temperature is 5 to 300 seconds.
[0017] Furthermore, the solute of the specific organic solution includes one of benzene, naphthalene, anthracene, n-butyl chloride, methyl chloride, isopropyl bromide, tert-butyl chloride, chlorobenzene, and bromobenzene; the solvent of the specific organic solution includes one of cyclohexane, tetrahydrofuran, pentane, ethyl ether, and ethylene glycol dimethyl ether.
[0018] Furthermore, the concentration of the specific organic solution is 0.1 to 10 mol / L.
[0019] Furthermore, the obtained lithium alloy negative electrode is immersed in a specific organic solution for a period of 1 to 300 minutes.
[0020] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0021] First, in view of the technical problems existing in the above-mentioned prior art and the difficulty in solving the problems of the present invention, the present invention closely combines the technical solutions to be protected and the results and data in the research and development process, and analyzes in detail and deeply how the technical solutions of the present invention solve the technical problems, and some creative technical effects brought about after solving the problems. The specific description is as follows:
[0022] The solid solution / intermetallic compound phase in the lithium alloy negative electrode of the present invention has good mechanical stability, provides an accommodation space for the deposition of metallic lithium in the reserved space, and is beneficial to maintaining the stability of the negative electrode macroscopic structure and the constancy of the volume during the charge and discharge process.
[0023] The lithium alloy negative electrode of the present invention has a double-layer structure. The lithium-philic alloy of the lower layer can induce the deposition of metallic lithium from bottom to top. The reserved alloy skeleton layer of the upper layer provides a stable three-dimensional skeleton for the deposition of metallic lithium, inducing the metallic lithium to achieve conformal deposition. The synergistic effect of the upper and lower layers ensures the uniform deposition of metallic lithium and the growth of no lithium dendrites.
[0024] The three-dimensional skeleton reserved in the upper layer of the lithium alloy negative electrode of the present invention and the three-dimensional skeleton in the lithium alloy in the lower layer are an integrated structure, which not only has good intrinsic electronic conductivity, but also has good electrical contact between the two, greatly increasing the real specific surface area of the electrochemical reaction, reducing the actual current density, and is beneficial to improving the deposition behavior of metallic lithium.
[0025] Second, considering the technical solution as a whole or from the perspective of the product, the technical effects and advantages of the technical solution to be protected by the present invention are described in detail as follows:
[0026] The lithium alloy negative electrode with reserved space and integrated conductive skeleton provided by the present invention not only has a novel and simple preparation method, but also has a significant effect on improving the cycle performance of the battery. At the same time, the thickness of the reserved space skeleton layer can be strictly controlled by the concentration of the organic solution and the immersion time. It is suitable for rapid preparation by a roll-to-roll method and is convenient for commercial mass production applications.
[0027] Third, as auxiliary evidence of the inventiveness of the claims of the present invention, it is also reflected in the following important aspects:
[0028] (1) The expected benefits and commercial value of the technical solution of the present invention after transformation are:
[0029] Driven by the vigorous development of the new energy field, metal lithium has become a hot research material in energy storage materials. The present invention provides a new method for preparing a composite metal lithium negative electrode, which can obtain a composite metal lithium negative electrode with a reserved conductive skeleton layer of a specific thickness by controlling the concentration and immersion time of a specific organic solution, thereby realizing a simple and convenient operation to prepare a composite metal lithium negative electrode, and having good practical value.
[0030] (2) Whether the technical solution of the present invention overcomes technical prejudice:
[0031] Three-dimensional conductive skeleton is a common structure for inhibiting the growth of lithium dendrites, but most of them are constructed by non-in-situ methods and then compounded with metallic lithium to obtain a composite electrode. The present invention obtains the conductive skeleton in-situ directly inside the electrode, and the conductive skeleton and the electrode are an integrated structure with good contact, providing a new preparation method for a three-dimensional composite metallic lithium negative electrode with reserved space on the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the structure of a lithium alloy negative electrode with a reserved space and an integrated conductive skeleton provided by an embodiment of the present invention;
[0033] Figure 2 is a scanning electron microscope (SEM) image of a lithium alloy negative electrode material containing a reserved space provided in an embodiment of the present invention;
[0034] Figure 3 It is a comparison diagram of the electrochemical performance of a symmetrical battery assembled with a lithium alloy negative electrode material containing a reserved space and a symmetrical battery assembled with a pure lithium negative electrode provided by an embodiment of the present invention;
[0035] In the figure: 1. Alloy skeleton layer; 2. Lithium-rich alloy layer. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] In order to enable those skilled in the art to fully understand how to implement the present invention, the present invention is partly an explanatory embodiment that expands the technical solution of the claims.
[0038] like Figure 1-Figure 3 As shown, a lithium alloy negative electrode with a reserved space and an integrated conductive skeleton provided by an embodiment of the present invention includes:
[0039] A lithium-rich alloy layer 2 is provided under the alloy skeleton layer 1, and a three-dimensional skeleton formed by a lithium solid solution / intermetallic compound is contained in the lithium-rich alloy layer 2. The upper layer of the lithium alloy negative electrode is a reserved space formed by the remaining three-dimensional alloy skeleton and the interconnection of the gaps between the skeletons. The skeleton in the surface reserved space and the skeleton in the lithium alloy are both three-dimensional integrated skeleton structures formed in situ by lithium solid solution or intermetallic compound.
[0040] The lithium solid solution or intermetallic compound three-dimensional skeleton is formed in situ during the preparation of lithium alloys and is a continuous integrated structure.
[0041] The height of the reserved space on the surface, that is, the thickness of the alloy skeleton layer 1 reserved on the surface, is 1 to 100 μm.
[0042] The present invention also provides a method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton, and the specific preparation method comprises:
[0043] Step 1: Mix the dissimilar metal / non-metal with metallic lithium in a certain molar ratio, and melt them into a liquid at 300°C to 800°C to form a molten lithium-rich alloy;
[0044] Step 2: The obtained molten lithium-rich alloy is formed on a metal foil to obtain a lithium-rich dual-phase alloy layer with uniform thickness;
[0045] Step 3: preparing a specific organic solution that can react with metallic lithium;
[0046] Step 4: Soak the obtained lithium alloy negative electrode in a specific organic solution, and obtain reserved space layers with different thicknesses by controlling the solvent concentration and reaction time.
[0047] Dissimilar metals / non-metals include one or more of Cu, Al, Sn, Zn, Mg, Ca, Ba, Ag, In, Ge, Pb, Sb, C, and Si.
[0048] After obtaining a lithium-rich dual-phase alloy layer with uniform thickness, the time for cooling to room temperature is 5 to 300 seconds.
[0049] The solute of the specific organic solution includes one of benzene, naphthalene, anthracene, n-butyl chloride, methyl chloride, isopropyl bromide, tert-butyl chloride, chlorobenzene, and bromobenzene; the solvent of the specific organic solution includes one of cyclohexane, tetrahydrofuran, pentane, ethyl ether, and ethylene glycol dimethyl ether.
[0050] The concentration of the specific organic solution is 0.1 to 10 mol / L.
[0051] The obtained lithium alloy negative electrode is immersed in a specific organic solution for 1 to 300 minutes.
[0052] In order to prove the creativity and technical value of the technical solution of the present invention, the present invention part is an application example of the technical solution of the claims on specific products or related technologies.
[0053] The invention provides a lithium alloy negative electrode with a reserved space and an integrated conductive skeleton for use in a battery.
[0054] Example 1
[0055] CuLi60 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved conductive skeleton.
[0056] The preparation method of the lithium alloy negative electrode material comprises the following steps: placing metallic copper and metallic lithium in a crucible at a molar ratio of 1:60, heating the crucible to 500°C in an argon atmosphere to molten the metal mixture, coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium-copper alloy layer of uniform thickness; preparing a 2mol / L organic solution; immersing the obtained composite alloy in the prepared organic solution for 10 minutes, obtaining a nano-skeleton layer of about 10μm thickness on the surface of the alloy layer, and obtaining a final CuLi60 lithium alloy negative electrode material.
[0057] Instructions attached Figure 1 This is a schematic structural diagram of a lithium alloy composite negative electrode material containing a reserved inert skeleton layer in an embodiment of the present invention. The lower part of the entire composite negative electrode is a lithium-rich two-phase lithium-copper alloy composed of a metallic lithium phase and an inert lithium-copper solid solution alloy phase, and the lithium-copper solid solution alloy phase morphology is nanowire-like; the upper part of the entire composite negative electrode is composed of a reserved inert solid solution nanowire skeleton.
[0058] Instructions attached Figure 2 a is the surface SEM image of CuLi60 alloy before immersion in organic solution. It can be seen that lithium-copper solid solution nanowires are evenly distributed on the alloy surface, while other areas are filled with metallic lithium; Figure 2 b is the SEM image of the alloy surface of CuLi60 alloy after immersion in organic solution. The inert alloy skeleton layer is composed of a large number of lithium-copper solid solution nanowires. Figure 2 c is the SEM image of the alloy cross-section of the CuLi60 alloy after immersion in an organic solution. It can be seen that after immersion in the organic solution to remove the lithium single phase, the entire composite negative electrode is composed of a lower alloy layer and an upper inert skeleton layer; the lower alloy layer acts as a lithium-philic layer to induce metallic lithium to begin to deposit in the lower layer, and subsequent metallic lithium is continuously deposited from bottom to top, while the upper skeleton layer acts as a framework to accommodate the deposition of metallic lithium, making the deposition of metallic lithium more uniform and inhibiting the formation of lithium dendrites.
[0059] Figure 3 This is the electrochemical cycle performance test curve of the symmetrical battery of the lithium alloy negative electrode material synthesized in the above Example 1. The electrochemical cycle performance test adopts a Li-Li battery system, in which the electrode materials are all 10mm thin sheets cut from the lithium alloy negative electrode material with reserved space synthesized in the above Example 1, and a CR 2032 button battery model is used. In an ester electrolyte (1M LiTFSI (lithium bistrifluoromethanesulfonyl imide) is dissolved in EC (ethylene carbonate) / DEC (diethyl carbonate), v / v=1 / 1), 5% FEC (fluoroethylene carbonate) is added as an additive. Celgard 2325 type diaphragm, the test conditions are 1mA cm -2 The current density and 1 mAh cm -2 It can be seen that this lithium alloy negative electrode material with reserved space can greatly improve the cycle performance of the battery.
[0060] Embodiment 2:
[0061] AlLi2 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0062] The preparation method of the composite negative electrode material comprises the following steps: placing metallic aluminum and metallic lithium in a crucible at a molar ratio of 1:2, heating the crucible to 600°C in an argon atmosphere to molten the metal mixture, and then coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium-aluminum alloy with uniform thickness; then preparing a 2mol / L organic solution; and immersing the obtained lithium alloy in the prepared organic solution for 30 minutes, so that a solid solution alloy skeleton layer of about 30μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final AlLi2 lithium alloy negative electrode material.
[0063] Embodiment 3:
[0064] SnLi80 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0065] The composite negative electrode material preparation method comprises the following steps: placing metallic tin and metallic lithium in a crucible at a molar ratio of 1:80, heating the mixture to 400°C in an argon atmosphere to melt the metal mixture, and then coating the molten alloy on a stainless steel foil using a 40μm scraper to obtain a lithium-tin alloy with uniform thickness; then preparing a 2mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 20 minutes, so that a solid solution alloy skeleton layer of about 20μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final SnLi80 lithium alloy negative electrode material.
[0066] Embodiment 4:
[0067] The ZnLi30 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0068] The composite negative electrode material preparation method comprises the following steps: placing metallic zinc and metallic lithium in a crucible at a molar ratio of 1:30, heating the crucible to 800°C in an argon atmosphere to molten the metal mixture, and then coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium-zinc alloy with uniform thickness; then preparing a 2mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 20 minutes, so that a solid solution alloy skeleton layer of about 20μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final ZnLi30 lithium alloy negative electrode material.
[0069] Embodiment 5:
[0070] CaLi10 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0071] The composite negative electrode material preparation method comprises the following steps: placing metallic calcium and metallic lithium in a crucible at a molar ratio of 1:10, heating the crucible to 400°C in an argon atmosphere to molten the metal mixture, and then coating the molten alloy on a stainless steel foil using a 30μm scraper to obtain a lithium-calcium alloy with uniform thickness; then preparing a 0.5mol / L organic solution; and immersing the obtained lithium alloy in the prepared organic solution for 60 minutes, so that a solid solution alloy skeleton layer of about 15μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final CaLi10 lithium alloy negative electrode material.
[0072] Embodiment 6:
[0073] BaLi20 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0074] The composite negative electrode material preparation method comprises the following steps: placing metal barium and metal lithium in a crucible at a molar ratio of 1:20, heating the crucible to 500°C in an argon atmosphere to molten the metal mixture, and then coating the molten alloy on a stainless steel foil using a 100μm scraper to obtain a composite lithium-barium alloy with uniform thickness; then preparing a 1mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 40 minutes, so that a solid solution alloy skeleton layer with a thickness of about 20μm can be obtained on the surface of the alloy layer, thereby obtaining a final BaLi20 lithium alloy negative electrode material.
[0075] Embodiment 7:
[0076] AgLi50 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0077] The preparation method of the composite negative electrode material comprises the following steps: placing metallic silver and metallic lithium in a crucible at a molar ratio of 1:50, heating the crucible to 350°C in an argon atmosphere to molten the metal mixture, and then coating the molten alloy on a stainless steel foil using a 200μm scraper to obtain a lithium-silver alloy with uniform thickness; then preparing a 2mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 10 minutes, so that a solid solution alloy skeleton layer of about 10μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final AgLi10 lithium alloy negative electrode material.
[0078] Embodiment 8:
[0079] InLi10 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0080] The composite negative electrode material preparation method comprises the following steps: placing metal indium and metal lithium in a crucible at a molar ratio of 1:10, heating the crucible to 800°C in an argon atmosphere to melt the metal mixture, and then coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium-indium alloy with uniform thickness; then preparing a 2mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 30 minutes, so that a solid solution alloy skeleton layer of about 30μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final InLi10 lithium alloy negative electrode material.
[0081] Embodiment 9:
[0082] The GeLi5 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0083] The composite negative electrode material preparation method comprises the following steps: placing metallic germanium and metallic lithium in a crucible at a molar ratio of 1:5, heating the mixture to 600°C in an argon atmosphere to melt the metal mixture, and then coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium-germanium alloy with uniform thickness; then preparing a 1mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 30 minutes, so that a solid solution alloy skeleton layer of about 15μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final GeLi5 lithium alloy negative electrode material.
[0084] Embodiment 10:
[0085] PbLi60 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0086] The preparation method of the composite negative electrode material comprises the following steps: placing metal lead and metal lithium in a crucible at a molar ratio of 1:60, heating the crucible to 800°C in an argon atmosphere to molten the metal mixture, and then coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium-lead alloy with uniform thickness; then preparing a 2mol / L organic solution; and immersing the obtained lithium alloy in the prepared organic solution for 60 minutes, so that a solid solution alloy skeleton layer of about 50μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final PbLi5 lithium alloy negative electrode material.
[0087] Embodiment 11:
[0088] CuZnLi60 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0089] The composite negative electrode material preparation method comprises the following steps: placing metallic copper, metallic zinc and metallic lithium in a crucible at a molar ratio of 1:1:60, heating the mixture to 500°C in an argon atmosphere to melt the metal mixture, and then coating the molten alloy on a stainless steel foil using a 50μm scraper to obtain a lithium copper zinc alloy with uniform thickness; then preparing a 2mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 30 minutes, so that a solid solution alloy skeleton layer of about 30μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final CuZnLi60 lithium alloy negative electrode material.
[0090] Embodiment 12:
[0091] CuAgLi60 is immersed in a specific organic solution to corrode the metallic lithium phase to obtain a lithium alloy negative electrode material with a reserved skeleton.
[0092] The composite negative electrode material preparation method comprises the following steps: placing metallic copper, metallic silver and metallic lithium in a crucible at a molar ratio of 1:1:60, heating the mixture to 400°C in an argon atmosphere to melt the metal mixture, and then coating the molten alloy on a stainless steel foil using a 30μm scraper to obtain a lithium copper-silver alloy with uniform thickness; then preparing a 1 mol / L organic solution; and soaking the obtained lithium alloy in the prepared organic solution for 60 minutes, so that a solid solution alloy skeleton layer of about 30μm thickness can be obtained on the surface of the alloy layer, thereby obtaining a final CuAgLi60 lithium alloy negative electrode material.
[0093] The embodiments of the present invention have achieved some positive effects during the development or use process, and indeed have great advantages over the prior art. The following content is described in conjunction with data, charts, etc. of the test process.
[0094] The present invention soaks the composite metal lithium negative electrode in a specific organic solution to obtain a reserved integrated conductive skeleton. When the integrated conductive skeleton is used in a metal lithium battery, the reserved conductive skeleton can provide a space for the deposition of metal lithium and inhibit the growth of lithium dendrites. Figure 3 The electrochemistry of the mesosymmetric battery can verify the improvement of the electrochemical performance of the battery by this composite metal lithium negative electrode material with an integrated conductive skeleton with reserved space.
[0095] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A lithium alloy negative electrode having a reserved space and an integrated conductive skeleton, characterized in that: include: Alloy skeleton layer; A lithium-rich alloy layer is provided under the alloy skeleton layer, and the lithium-rich alloy layer contains a three-dimensional skeleton formed by a lithium solid solution / intermetallic compound. The upper layer of the lithium alloy negative electrode is a reserved space formed by the three-dimensional alloy skeleton remaining after the lithium single phase is selectively removed using a specific organic solution and the gaps between the skeletons. The skeleton in the reserved space on the surface and the skeleton in the lithium alloy are both three-dimensional integrated skeleton structures formed in situ by a lithium solid solution or an intermetallic compound.
2. The lithium alloy negative electrode with reserved space and integrated conductive skeleton according to claim 1, characterized in that: The lithium solid solution or intermetallic compound three-dimensional skeleton is formed in situ during the preparation of the lithium alloy and is a continuous integrated structure.
3. The lithium alloy negative electrode with reserved space and integrated conductive skeleton according to claim 1, characterized in that: The height of the reserved space on the surface, that is, the thickness of the alloy skeleton layer reserved on the surface, is 1 to 100 μm.
4. A method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton as claimed in any one of claims 1 to 3, characterized in that: The specific preparation method includes: Step 1: Mix the dissimilar metal / non-metal with metallic lithium in a certain molar ratio, and melt them into a liquid at 300°C to 800°C to form a molten lithium-rich alloy; Step 2: coating the obtained molten lithium-rich alloy on a metal foil to obtain a lithium-rich dual-phase alloy layer with uniform thickness; Step 3: preparing a specific organic solution that can react with metallic lithium; Step 4: Soak the obtained lithium alloy negative electrode in a specific organic solution, and obtain reserved space layers with different thicknesses by controlling the solvent concentration and reaction time.
5. The method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton according to claim 4, characterized in that: The dissimilar metals / non-metals include one or more of Cu, Al, Sn, Zn, Mg, Ca, Ba, Ag, In, Ge, Pb, Sb, C, and Si.
6. The method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton according to claim 4, characterized in that: The time for cooling to room temperature after obtaining the lithium-rich dual-phase alloy layer with uniform thickness is 5 to 300 seconds.
7. The method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton according to claim 4, characterized in that: The solute of the specific organic solution includes one of benzene, naphthalene, anthracene, n-butyl chloride, methyl chloride, isopropyl bromide, tert-butyl chloride, chlorobenzene, and bromobenzene; the solvent of the specific organic solution includes one of cyclohexane, tetrahydrofuran, pentane, ether, and ethylene glycol dimethyl ether.
8. The method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton according to claim 4, characterized in that: The concentration of the specific organic solution is 0.1-10 mol / L.
9. The method for preparing a lithium alloy negative electrode having a reserved space and an integrated conductive skeleton according to claim 4, characterized in that: The obtained lithium alloy negative electrode is immersed in a specific organic solution for 1 to 300 minutes.
Citation Information
Patent Citations
Copper nanowire and preparation method thereof
CN109332719A
Composite negative pole piece, preparation method thereof and lithium ion battery
CN111900332A